2013
DOI: 10.4081/ijas.2013.e26
|View full text |Cite
|
Sign up to set email alerts
|

Management Risk Factors for Calf Mortality in Intensive Italian Dairy Farms

Abstract: High calf mortality is an important factor of economic loss in dairy production. At present, limited data are available on calf rearing practices and calf mortality in Italian dairy farming. The aim of the study was to identify the most important management risk factors for preweaning calf mortality in Italian dairy farms. A group of 28 intensive dairy farms from Lombardy (Italy) were visited to collect information about calf management and calf mortality. Female calf mortality showed high variability among he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 18 publications
5
24
2
Order By: Relevance
“…Stillbirth rate and calf mortality in this survey were similar to that reported in a survey of intensive dairy farms in Italy (Zucali et al, 2013), and higher than that in a survey of pasture-based farms in New Zealand (Cuttance et al, 2017). Calf mortality rates vary substantially among studies, as shown by significant heterogeneity (Cochrane's Q test) in a systematic review and meta-analysis conducted by Compton et al (2017).…”
Section: Stillbirths and Heifer Mortalitysupporting
confidence: 78%
“…Stillbirth rate and calf mortality in this survey were similar to that reported in a survey of intensive dairy farms in Italy (Zucali et al, 2013), and higher than that in a survey of pasture-based farms in New Zealand (Cuttance et al, 2017). Calf mortality rates vary substantially among studies, as shown by significant heterogeneity (Cochrane's Q test) in a systematic review and meta-analysis conducted by Compton et al (2017).…”
Section: Stillbirths and Heifer Mortalitysupporting
confidence: 78%
“…By law, calves are allowed to be kept in individual pens up to 8 weeks of age, covering the majority of the preweaning period, if not otherwise specified by the veterinarian [40]. According to previous studies, housing calves in individual calf pens in early life is known to protect for mortality compared with group housing, where the risk of mortality tends to increase with group size [20,21,25,33,41].…”
Section: Risk Factors Associated With Calf Mortality Ratementioning
confidence: 99%
“…Numerous studies have arrived at the conclusion that on-farm mortality has a high between-herd variation [11,25,26], indicating that dairy cattle health and welfare vary heavily across herds and it would therefore be worthwhile to analyse the differences in their management systems. Identifying herd-level risk factors for onfarm mortality is highly relevant for many stakeholders such as farmers, veterinary advisors and authorities, and of great value especially for larger herds where intervention can positively affect a larger number of animals.…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded form this result that nearly all farmers of the study area had a fair knowledge about timing of colostrums feeding. However, it was observed that if calves receive colostrums by suckling than those fed using other methods, have a higher mortality rate (Gulliksen et al, 2009) and a delay in colostrums feeding increases calf mortality (Zucali et al, 2013). Moreover, the odds of having diarrhea was higher in calves <3 months of age that was provided colostrums by suckling (Svensson et al, 2003).…”
Section: Advances In Animal Andmentioning
confidence: 99%